Juridical Review of Implementation of Law of the Republic of the Philippines No. 11479 concerning Anti-Terrorism seen from the Perspective of International Law of Human Rights - Andre Oktavianus Masang (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Andre Oktavianus Masang, Herman Suryokumoro, Yasniar Rachmawati MadjidFaculty of Law Universitas Brawijaya Jl. MT Haryono No. 169 MalangEmail: andreoktavianus4@gmail.comAbstractTerrorism network is expanding along with the time, and the implications it brings are perceived by notonly a country but also some others, resulting in instability of economy, disrupted sovereignty, andpotential of political threats. The growth of the terrorism network is inextricable from information andcommunication media and social media that allow easier recruitment of terrorists and brainwashing intothe doctrine of terrorism. The development of transportation has also supported the movement of theterrorists to give even wider access to supply of weapons from organisations or parties as their allies,as what has been experienced by the southern Philippines. The effectuation of the Law of the Republicof the Philippines Number 11479, however, cannot be considered as enforcement to fight againstterrorism since some articles in the law have a broad scope of meaning regarding terrorism and thereare indications of power abuse that tends to hamper the freedom to express and opine. This tendencycould lead to the violation of international human rights. Thus, formulation of the national law in thePhilippines according to the enforcement of human rights is required. Several regulations regardinginternational human rights of ASEAN related with the violation in the Law of the Republic Number11479 involve International Covenant on Civil and Political Rights (ICCPR), Universal Declaration ofHuman Rights  (UDHR), ASEAN Human Rights Declaration, ASEAN Intergovernmental Commissionon Human Rights (AICHR). Keywords: Law of the Republic Number 11479, UDHR, ICCPR, AICHR, ASEAN Human RightsDeclarationAbstrakSeiring semakin berkembangnya zaman, berkembang pula perluasan jaringan terorisme yangdimana tidak hanya dirasakan oleh satu negara saja namun dampak yang ditimbulkan daripekembangan terorisme tersebut dapat dirasakan oleh negara lain yang berakibat padaketidakstabila ekonomi, kedaulatan wilayah yang terganggu dan tmbulnya ancaman politik.Perkembangan terorisme tidak lain di dukung oleh media informatika, media sosial yang dimana perekrutan anggotanya dapat dilakukan dengan mudah dan melakukan doktrin ataupemahaman mengenai terorisme dengan sangat mudah. Media transportasi yang saat inisemakin berkembang menyebabkan pelaku tindak terorisme dapat dengan mudahnyaberpergian dari satu tempat ke tempat lain dan memaosk persenjataan yang di miliki denganmudahnya dari pihak yang mendukung kelompok atau organisasi tertentu seperti yang di alamioleh negara Filipina bagian selatan. Namun penetapan Undang-Undang Republik Nomor11479 pemerintah Filipina, tidak dapat dikatakan sebagai peneegakan dalam memerangiterorisme, dikarenakan masih terdapat beberapa pasal di dalam peraturan tersebut yangmemiliki pemahaman mengenai terorisme yang sangat luas dan indikasi penyalahgunaankekuasaan yang berdampak pada pembatasan kebebasan berpendapat dan berekspresi yangmengarah pada pellanggaran hak asasi manusia (HAM) internasional, sehingga diperlukanadanya perumusan suatu perundang-undangan bagi hukum nasional Filipina yang berdasarkanpada penegakan hak asasi manusia. Beikut beberapa peraturan hak asasi manusia internasionalhak asasi manusia ASEAN yang berhubungan dengan indikasi pelanggaran di dalam Undang Undang Republik Nomor 11479, International Covenanton Civil and Political Rights(ICCPR) atau hak-hak sipil dan politik, dan Universal Declaration Human Rights (UDHR) atauDeklarasi Universal Hak Asasi Manusia (DUHAM), Deklarasi Hak Asasi Manusia ASEAN,ASEAN Intergovermental Commission on Human Rights (AICHR).Kata Kunci: Undang-Undang Republik Nomor 11479, DUHAM, ICCPR, AICHR, DeklarasiHak Asasi Manusia ASEAN.